Approximation of a bounded solution of a linear difference equation on Z2 by solutions of corresponding boundary-value problems in a Banach space - Gorodnii, M. F. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study the problem of existence and uniqueness of solutions of boundary-value difference problems in a Banach space that correspond to a certain difference equation on Z2. We prove a theorem on approximation of the unique bounded solution of the considered equation by solutions of the corresponding boundary-value problems.